SISTEM INFORMASI DESA NEGARA TULANG BAWANG KECAMATAN BUNGA MAYANG KABUPATEN LAMPUNG UTARA BERBASIS WEB - Machudor Yusman; Akmal Junaidi; Dwi Sakethi; Rendi Adam (Jurnal Pepadun, 2020)
Population data management is a very important thing in a government agency. Information about the village is important to provide information to the community. This research was conducted in Tulang Bawang State village of Bunga Mayang district of North Lampung. Currently, the management of population data is still done by conventional, by storing data in the form of documents recorded. To facilitate the management of such data, it is necessary to make the village information system fast and accurate. This system uses waterfall development method. Analysis, design, recording, testing, and maintenance. The result of the evaluation of the village information system of Tulang Bawang State, the assessment for satisfaction is at an average of 78.38% aspect of the display or in category good. The test results showed that the functions in the village information system of Tulang Bawang state have been able to run well according to what was given. So it can be concluded that the system is working well to help the village staff work in the management of population data and make logging more accurate.